Battery-type CuCo2O4/CuO nanocomposites as positive electrode materials for highly capable hybrid supercapacitors. Issue 17 (1st September 2021) - Mao, Hui; Sun, Jiale; Bao, Enhui; Dai, Longjun; Xu, Chunju; Chen, Huiyu
Abstract: In this work, CuCo2 O4 /CuO composites with morphologies of urchin-like microstructures and octahedrons were obtained, respectively, through a simple hydrothermal reaction combined with extra annealing conversion of precursors. The microstructure and chemical composition of the composites were investigated in detail by SEM, TEM, XRD, and XPS techniques. The electrochemical tests indicate that the CuCo2 O4 /CuO composites exhibit typical electrochemical signatures of battery-like materials. The urchin-like microstructures deliver a higher capacity of 298.92C g -1 than that of octahedrons in the three-electrode configuration. Furthermore, a hybrid supercapacitor (HSC) device was fabricated based on activated carbon (AC) and the CuCo2 O4 /CuO composite. The urchin-like CuCo2 O4 /CuO//AC HSC delivered an energy density of 28.12 Wh kg -1 under 874.87 W kg -1 and exceptional cyclic stability with 106.49% capacity preservation after 5000 cycles. In comparison, the CuCo2 O4 /CuO octahedrons//AC HSC exhibited 26.04 Wh kg -1 at 899.27 W kg -1 . Due to these extraordinary properties, urchin-like CuCo2 O4 /CuO composites may serve as very feasible candidates for highly capable supercapacitors in the near future.